PERANCANGAN SISTEM PAKAR IDENTIFIKASI JENIS IKAN MAS KOKI MENGGUNAKAN METODE FORWARD CHAINING BERBASIS ANDROID - Andre Renaldy Sihombing (TeIKa, 2020)
Goldfish are loved by ornamental goldfish enthusiasts in education and the general public. Goldfish in Indonesia, there are several types of popular goldfish that people often keep. As a layman, sometimes he is still confused about the types of goldfish he meets. The name of the type of goldfish in one area is usually different from the name in another area, even though it is from the same type of goldfish. This makes it difficult for fellow goldfish lovers or fish farmers who deal with goldfish as a business in the world of ornamental fish. It takes a goldfish expert who is experienced in identifying types of goldfish. In fact, the number of goldfish experts is very small, making it difficult to find at any time. The solution offered is by designing an expert system application that can identify types of goldfish based on android which can identify types of fish based on body shape, tail, eyes, head and color of the goldfish. This study uses the System Development Life Cycle (SDLC) method as an application design method, and the identification method uses forward chaining. The conclusion of this research is the application of identification of types of goldfish helps goldfish lovers in finding the type of goldfish correctly. Applications made produce an accuracy of 87.5% with a system inaccuracy of 12.5%. The suggestion from this research is that it is hoped that this application can be made and used by using the image recognizer on goldfish so that this application can be more easily used by goldfish lovers in identifying the type of goldfish desired in the future.